"Structural Injustice" as an analytical tool. Issue 10 (24th September 2021) - Sankaran, Kirun
Abstract: "Structural Injustice" refers to injustices that can't be attributed to particular actions by bad actors. This article surveys Iris Marion Young's influential account of structural injustice; lays out some considerations related to the concept's use as an analytical tool; and critically surveys Young's account of individual responsibility for structural injustice.